A comprehensive analysis identifies and validates NPC1 as a potential biomarker for prognosis in HCC - Lu, Xingjun; Gou, Tianyao; He, Xuxing; Chen, Xia; Yang, Daqing; Peng, Xiaozhen (Frontiers in Genetics, 2025)
Niemann-Pick type C1 protein (NPC1), a key regulator of intracellular cholesterol transport and a transmembrane protein, has been implicated in carcinogenesis, particularly in hepatocellular carcinoma (HCC). Despite the noted association, the specific role of NPC1 in HCC remains underexplored. In this study, we conducted a comprehensive analysis of NPC1 expression across diverse gene expression databases to elucidate its prognostic significance and functional interactions. Utilizing LinkedOmics for co-expression network analysis and KEGG for functional enrichment, we identified a set of genes co-expressed with NPC1 and its associated biological pathways. Our findings demonstrate that NPC1 is frequently upregulated and amplified in HCC tumor tissues, with higher expression levels significantly associated with reduced overall survival (OS), progression-free survival (RFS), and disease-free survival (DFS). Functional enrichment analysis of the top 50 positively correlated genes with NPC1 highlighted significant enrichment in pathways related to organelle fission, nuclear division, chromosomal region spindle formation, and centrosome function, suggesting a role for NPC1 in DNA replication processes. These findings establish a correlation between NPC1 expression and HCC prognosis, laying the groundwork for future studies to explore the therapeutic potential of NPC1 inhibition in HCC.